The role of zinc supplementation for diarrhoea in children: a critical review (Bangladesh Journal of Medical Science, 2019)
Background: Nearly 1.7 million children suffer from diarrhoea and around 760,000 die each year. The high prevalence of diarrhoea in the developing countries is closely related to lack of safe drinking water, inadequate sanitation and hygiene, and poor health and nutritional status. These environmental conditions facilitate the spread of infectious disease easily. The great morbidity and mortality of this preventable and treatable disease raise concern on how to save children from this fatal disease by improving management of diarrhoea. Several studies suggest that zinc deficiency contribute towards high morbidity and mortality in diarrhoea. Further, there is an area of uncertainty regarding how significant zinc supplementation will help to reduce the duration and severity of diarrhoea in children compared to the diarrhoea management without zinc?Objective: To critically analyse the current evidences of zinc supplementation in diarrhoea.Data Sources: Keywords searching through MEDLINE Ovid database and additional references from retrieved articles. Study Selection: Limited to randomized controlled trial(RCT) study design and systematic review studies which were conducted from 2006 to 2016. However, there is one prospective cohort study included as it is a follow-up of subjects who participated in the previous double-blind randomized placebo-controlled trial.Data Synthesis: This review involves a summary of 10 articles that have been appraised on their relevance in evaluating the role of zinc in reducing severity and duration of diarrhoea in children. Further, the literature found is synthesised through method used in the studies and the effectiveness of zinc therapyConclusion: Zinc is relatively safe to be used and it can improve diarrhoea management especially in developing countries.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.190-195